Advanced liver fibrosis effects on the response to sofosbuvir‐based antiviral therapies for chronic hepatitis C. Issue 12 (13th August 2018) - Morio, Kei; Imamura, Michio; Kawakami, Yoshiiku; Nakamura, Yuki; Hatooka, Masahiro; Morio, Reona; Fujino, Hatsue; Nakahara, Takashi; Murakami, Eisuke; Kawaoka, Tomokazu; Tsuge, Masataka; Hiramatsu, Akira; et al.
Abstract : Background: Sustained virological response (SVR) rates for the treatment of chronic hepatitis C virus (HCV)–infected patients have drastically improved with the use of direct‐acting antiviral (DAA) therapies; however, a small minority of patients still fails to eradicate the virus. We analyzed factors associated with SVR in DAA therapy and the effect of age and liver fibrosis on treatment response. Methods: Nine hundred and eighteen patients with chronic HCV infection were treated with 24 weeks of daclatasvir plus asunaprevir (DCV + ASV) or 12 weeks of sofosbuvir plus ledipasvir (SOF + LDV), ombitasvir, paritaprevir plus ritonavir (OMB + PTV + r) or sofosbuvir plus ribavirin (SOF + RBV). Multivariate logistic regression analysis was used to identify factors associated with SVR. The effect of age and liver fibrosis on SVR was analyzed. Results: The overall SVR rate was 95.4% (876 of 918 patients), and rates by DAA regimen were 93.4%, 95.7%, 100%, and 95.0% in DCV + ASV‐treated, SOF + LDV‐treated, OMB + PTV + r‐treated, and SOF + RBV‐treated patients, respectively. Patients older than 75 years achieved a similar SVR rate with those aged 75 years or younger (96.4% and 94.8%, respectively). Multivariate logistic regression analysis identified absence of DAA therapy history (odds ratio [OR], 3.868 for presence; P = 0.002) and FIB‐4 index of less than 3.25 (OR, 5.042 for ≥3.25; P = 0.001) as independent predictors for SVR. SVR rates were significantly lower in patients with FIB4 index of 3.25 or more compared with those with less than 3.25, especially in sofosbuvir‐based therapies such as SOF + LDV‐treated or SOF + RBV‐treated patients. Conclusion: Both older and younger patients respond similarly to DAA therapy. Advanced liver fibrosis affects the virological response to sofosbuvir‐based therapy.